Evaluation of Serum Lipids and Castelli Risk Indexes of Cutaneous Lichen Planus Patients: A Retrospective Case– Control Study - Kazan, Didem (Cerrahpaşa Medical Journal, 2024)
Objective: Lichen planus (LP) is a cutaneous inflammatory disease, and accompanying dyslipidemia may be detected in LP patients. This study aimed to examine cardiovascular disease (CVD) markers and dyslipidemia in LP patients and compare them with healthy controls. Methods: Forty-four patients aged older than 18 years old with histopathologically confirmed classical cutaneous LP, and 44 age- and gender-matched healthy controls admitted to the dermatology outpatient clinic between June 2022 and March 2023 were included in the study. All patients’ demographic features, serum triglyceride, total cholesterol (TCOL), low-density lipoprotein cholesterol (LDL), and high-density lipoprotein cholesterol (HDL) values, and Castelli-1 (TCOL/HDL) and Castelli-2 (LDL/HDL) risk indexes are recorded in the case report files. Results: The number of patients with normal LDL values in the study group is significantly lower than in the control group (13.6% vs. 36.4%, P = .034). And also, 38 (86.4%) patients in the study group have higher Castelli-1 risk indexes than the controls (P = .014). Conclusion: Lichen planus has a systemic, chronic inflammatory process. As a result of sharing common inflammatory processes, CVD and dislipidemia may be associated with LP. Therefore, serum lipid levels should be checked in the first evaluation and follow-up of LP patients. Cite this article as: Kazan D. Evaluation of serum lipids and Castelli risk indexes of cutaneous lichen planus patients: A retrospective case–control study. Cerrahpaşa Med J. 2024;48(1):64-66.